CD19 CAR-T Cell Therapy Induced Immunotherapy Associated Interstitial Pneumonitis: A Case Report - Sun, Zhuanyi; Xie, Caiqin; Liu, Hui; Yuan, Xianggui (Frontiers in Immunology, 2022)
Background Chimeric antigen receptor-modified T cells (CAR-T) targeting CD19 has produced a high durable response in refractory or relapsed diffuse large B-cell lymphoma. Besides well-known cytokine release syndrome (CRS) or immune effector cell–associated neurotoxicity syndrome during CAR-T cell therapy, there were several rarely encountered fatal complications. Case Report A 63-year-old male patient with refractory EBV-positive diffuse large B-cell lymphoma, developed interstitial pneumonitis with prolonged hypoxemia at 16 weeks after CD19 CAR-T cell therapy. There was no evidence of CRS and any infections. The patient recovered after intravenous immunoglobulin without tocilizumab or glucocorticoid administration. Now he is still in remission without interstitial pneumonitis 3 years after CAR-T cell therapy. Conclusion This is the first report of immunotherapy-associated interstitial pneumonitis after CAR-T cell therapy. Our finding suggested the importance of careful follow-up and proper treatments for immunotherapy-associated pneumonitis in the CAR-T cell therapy schedule.